Poncelet's porism: a long story of renewed discoveries, II - Del Centina, Andrea (Archive for history of exact sciences, 2016)
The first part of the article appeared in the previous issue of this journal. It deals with the history of the research on Poncelet's porism, and related subjects, which were developed from the middle of the eighteenth century until the end of the nineteenth century. In this second part, we take the research developed in the twentieth century. We also offer a comparison of the main works on the subject, and we draw some conclusions.